2017
DOI: 10.1016/j.talanta.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Development of pH-responsive polymer and citrate aqueous two-phase system for extractive bioconversion of cefprozil

Abstract: A pH-responsive aqueous two-phase system (pH-ATPS) has been developed by sodium citrate and a recyclable pH-responsive polymer P that can response to the change of pH values. Phase separation mechanism is studied through Low field-NMR. All variables affecting the phase separation are evaluated. Phase characteristics (viscosity, density, interfacial tension) and phase separation kinetic are studied for understanding of separation process and operational parameters in applications. This pH-ATPS has the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…UCON has been employed for extraction of PEGylated lysozyme [52], protein purification [53], and purification of antibodies such as IgG [54]. Dong et al used a mixture of two pHresponsive polymers including P ADB4.91 and P ADB4.06 for extraction of transglutaminase [55], while Chen et al used P ADB6.8 as a pH-responsive polymer for cefprozil extractive bioconversion [56]. More applications of smart polymers in extraction and sample preparation of enzymes, hormones, and macromolecules are expected in the future.…”
Section: Homogeneous Phase Formation Using Smart Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…UCON has been employed for extraction of PEGylated lysozyme [52], protein purification [53], and purification of antibodies such as IgG [54]. Dong et al used a mixture of two pHresponsive polymers including P ADB4.91 and P ADB4.06 for extraction of transglutaminase [55], while Chen et al used P ADB6.8 as a pH-responsive polymer for cefprozil extractive bioconversion [56]. More applications of smart polymers in extraction and sample preparation of enzymes, hormones, and macromolecules are expected in the future.…”
Section: Homogeneous Phase Formation Using Smart Polymersmentioning
confidence: 99%
“…Using traditional polymers in large-scale extraction is rare, because of the high cost. So, the ability of smart polymers to be recycled substantially reduces the extraction cost and makes them a suitable alternative to commonly known polymers [55,56,123]. Bai et al [123] relied on using a pH-responsive polymer for efficient extraction of N-glycoprotein/glycol peptide as indicated in Figure 3A.…”
Section: Ph-induced Phase Separationmentioning
confidence: 99%
“…The relaxation time was higher than the T22 relaxation time of PADB4.78 alone due to the presence of PN in the bottom phase. Such difference among the water-binding capability of polymers led to the occurrence of repulsion, reflecting the feasibility in forming aqueous two-phase system [6,32].…”
Section: Lf-nmr T2 Relaxation Time Measurementmentioning
confidence: 99%
“…ABS are endowed with a water-rich environment and an operating condition-dependent behavior, being deemed as mild extraction/separation processes. It has been shown that ABS can be used in several integrated biotech-based processes, such as in extractive bioconversions, , enzymatic reactions, and biopharmaceutical manufacturing . Furthermore, following the addition of ionic liquids (ILs) as ABS components, significant improvements have been accomplished in the efficiency, yield, and selectivity of numerous extraction and separation processes .…”
Section: Introductionmentioning
confidence: 99%